Ultrastructure of Naegleria fowleri enflagellation. - Patterson, M (1981)
Amoebae of Naegleria fowleri nN68 became elongated flagellated cells 150 to 180 min after subculture to non-nutrient buffer. N. fowleri NF69 did not become elongated or flagellated under these conditions. Electron microscopic examination of N. fowleri confirmed that it is a typical eucaryotic protist with a distinct nuclear envelope and prominent nucleolus, numerous vacuoles and cytoplasmic inclusions, pleomorphic mitochondria, and some rough endoplasmic reticulum. During incubation in non-nutrient buffer, both strains lost ultraviolet-absorbing material to the medium, and the number of vacuoles decreased. In strain nN68, basal bodies, a rootlet, and flagella are formed quickly after an initial lag of 90 min. Initially, the rootlet is not associated with the nucleus but they become associated subsequent at the leading end of the elongated cell. In elongated cells, the rootlet lies in a furrow or groove extending the length of the nucleus. Flagella of N. fowleri nN68 exhibit the typical 9 + 2 arrangement of filaments and are surrounded by a sheath which is continuous with the plasma membrane. The enflagellation process in N. fowleri can be manipulated reproducibly.